2004
DOI: 10.1088/0953-8984/16/14/017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high pressure on nitrogen compounds of milk

Abstract: The effect of pressurization at different pressures (from 200 to 1000 MPa, at 200 MPa intervals, t const. = 15 min) and periods of time (from 15 to 35 min, at 10 min intervals, p const. = 800 MPa) on the changes of proteins and nitrogen compounds of skimmed milk was studied.The pressurization caused an increase in the amount of soluble casein and denaturation of whey proteins. The level of nonprotein nitrogen compounds and proteoso-peptone nitrogen compounds increased as a result of the highpressure treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…A study by Li et al 50 found that bovine milk treated by HPP retains bovine IgG activity when pressure is lower than 276 MPa. Kielczewska et al 51 evaluated the influence of pressurization on nitrogen compounds in bovine milk and found a 17% decrease in unspecified immunoglobulin activity following treatment at 200 MPa for 15 minutes at 20°C. Immunoglobulins and α-lactalbumins in goat's milk were shown to be pressure resistant under pressures of 300 MPa at 25°C, partially denatured when temperature was increased to 50°C, and subsequently denatured by 35% upon exposure to 500 MPa of pressure.…”
Section: Effect Of High-pressure Processing On Iga Immunoactivitymentioning
confidence: 99%
“…A study by Li et al 50 found that bovine milk treated by HPP retains bovine IgG activity when pressure is lower than 276 MPa. Kielczewska et al 51 evaluated the influence of pressurization on nitrogen compounds in bovine milk and found a 17% decrease in unspecified immunoglobulin activity following treatment at 200 MPa for 15 minutes at 20°C. Immunoglobulins and α-lactalbumins in goat's milk were shown to be pressure resistant under pressures of 300 MPa at 25°C, partially denatured when temperature was increased to 50°C, and subsequently denatured by 35% upon exposure to 500 MPa of pressure.…”
Section: Effect Of High-pressure Processing On Iga Immunoactivitymentioning
confidence: 99%
“…Milk pH is associated with micellar and soluble phosphate and calcium salt balance (Kielczewska et al ., ) and also with acid concentration, which can be produced from lactose and from lipid enzymatic hydrolysis resulting in free fatty acids (Pareda et al ., ; Serra et al ., ). The results obtained for homogenised milk at pressures up to 300 MPa showed no significant pH reduction ( P > 0.05) after the HPH and also during 2 days of storage (data not shown).…”
Section: Resultsmentioning
confidence: 85%
“…Kiełczewska et al. (2004) reported that for cows’ milk the level of whey protein denaturation achieved after 15 min HPP treatment at 400 MPa was 35.7%, and this increased to just 51.1% at 600 MPa. HPP leads to unfolding and aggregation of whey proteins, which is accompanied by an increase in water‐binding capacity.…”
Section: Assessmentmentioning
confidence: 99%
“…In an experiment where 600 MPa for 15 min were applied to achieve a reduction of at least 7 log 10 cycles of three food‐borne bacteria ( L. monocytogenes , S. aureus and Pseudomonas aeruginosa ) about 80% of the β‐Lg was denatured (Ramos et al., 2015). Temperature increases the level of denaturation, achieving 100% in milk treated at 400 MPa and above and temperatures up to 60°C (Garcia‐Risco et al., 2000; Kiełczewska et al., 2004; Moatsou et al., 2008a).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation